2022
DOI: 10.1186/s12865-022-00487-3
|View full text |Cite
|
Sign up to set email alerts
|

Helios expressing regulatory T cells are correlated with decreased IL-2 producing CD8 T cells and antibody diversity in Mozambican individuals living chronically with HIV-1

Abstract: Background Human immunodeficiency virus type 1 (HIV-1) causes impairment of T and B cell responses, which begins during the acute phase of infection and is not completely restored by antiretroviral treatment. Regulatory T cell (Tregs) can improve overall disease outcome by controlling chronic inflammation but may also suppress beneficial HIV-1 specific immune responses. We aimed to analyze the profile of Tregs and their correlation with the status of T cells activation, the expression of IL-2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…CD8 + cells can protect against atherosclerosis by inducing plaque cell apoptosis and inflammation ( 50 ). A number of HIV antigens are recognized by antibodies which are correlated inversely with CD8 + T cell activation and positively with CD4 + cell counts ( 51 ). Early research showed that PLWH share some markers of aging with older noninfected patients, such as increased inflammation marker levels, D-dimers, CD4 + /CD8 + inversion, and proportions of memory CD8 + T cells ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…CD8 + cells can protect against atherosclerosis by inducing plaque cell apoptosis and inflammation ( 50 ). A number of HIV antigens are recognized by antibodies which are correlated inversely with CD8 + T cell activation and positively with CD4 + cell counts ( 51 ). Early research showed that PLWH share some markers of aging with older noninfected patients, such as increased inflammation marker levels, D-dimers, CD4 + /CD8 + inversion, and proportions of memory CD8 + T cells ( 52 ).…”
Section: Discussionmentioning
confidence: 99%